2017
DOI: 10.2528/pierc17060502
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Band Polarization-Insensitive Metamaterial Inspired Microwave Absorber for Lte-Band Applications

Abstract: Abstract-In this paper, the design, simulation and measurement of a dual-band polarizationinsensitive metamaterial inspired microwave absorber are presented. The unit cell is composed of two concentric closed ring resonator (CRR) structures forming octagonal rings which are carved on an FR-4 dielectric substrate to give maximum absorption at dual frequencies of 2.09 GHz and 2.54 GHz. At these frequencies, the minimum reflection coefficients of −29.15 dB and −18.76 dB are achieved with absorption rates of 99.88… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Lesser value of S 11 represents more desired absorption of MA. Most of the proposed metamaterial absorbers have a square array of 2D-bravais lattice with a square geometry of the unit cell [6][7][8][9][10][11][12][13][14][15][16][17][18]. Square geometry has lower degree of symmetry than that of hexagonal.…”
Section: Design Of Unit Cell Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Lesser value of S 11 represents more desired absorption of MA. Most of the proposed metamaterial absorbers have a square array of 2D-bravais lattice with a square geometry of the unit cell [6][7][8][9][10][11][12][13][14][15][16][17][18]. Square geometry has lower degree of symmetry than that of hexagonal.…”
Section: Design Of Unit Cell Structurementioning
confidence: 99%
“…It has found many novel applications such as cloaking [2], filters [3], and antennas [4]. After the first proposed Metamaterial Absorber (MA) by Landy et al in 2008 [5], many such MAs which have single and multiband absorption properties have been proposed [6][7][8][9][10][11][12]. MAs have many advantages such as ultra-thin and lightweight compared to conventional absorbers which are bulky and fragile.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the single band, dualband and multiband absorbers are reported by researchers. In line of this, Jamilan et al and Kaur et al, presented a dual‐band metamaterial absorber but the size of unit cell is extremely large. Moreover, absorber reported in Reference , fulfills the demand of compact size, however equivalent circuit modeling of the absorber for better insight of the design is not illustrated.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, equivalent circuit model of the proposed absorber is drawn with the help of surface current distributions and electric field distributions. The comparison between proposed absorber and other available designs in References are given in Table . From Table 1, it is confirmed that the proposed design in very prominent structure in terms of size, thickness, high peak absorption, and ease of fabrication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation